(untitled) (Research, Society and Development, 2020)
The Inquiry-Based Science Teaching (EnCI) is an approach that enables the student to build knowledge actively and with satisfactory results in learning. This work aimed to analyze EnCI’s contributions to student learning in basic education. A systematic review of the literature in the Capes Periodicals and Capes Thesis and Dissertation Catalogue platforms was carried out. In the search platforms the words used for the search were: teaching, science, research, learning. The initial analysis was done through the title, abstract and keywords. The selected papers were read in full and a spreadsheet in Excel was used to organize the extracted data. In total 37 works were examined. Based on the analyses made EnCI favors the learning of students in Basic Education, because it allows space for problematizations and discussions. The differentiated activities generally promote the engagement and autonomy of the students, and ultimately favors scientific literacy.